Annual Update in Intensive Care and Emergency Medicine 2017 - Vincent, Jean-Louis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The Annual Update compiles reviews of the most recent developments in experimental and clinical intensive care and emergency medicine research and practice in one comprehensive reference book. The chapters are written by well recognized experts in these fields. The book is addressed to everyone involved in internal medicine, anesthesia, surgery, pediatrics, intensive care and emergency medicine.
Common Abbreviations -- Part I Infections -- Part II Sepsis -- Part III Fluids -- Part IV Renal Issues -- Part V Metabolic Support -- Part VI Cardiac Conditions -- Part VII Cardiopulmonary Resuscitation -- Part VIII Oxygenation and Respiratory Failure -- Part IX Neurological Conditions -- Part X Burn Patients -- Part XI Drug Development and Pharmaceutical Issues -- Part XII The Extremes of Age -- Part XIII Simulation -- Part XIV Organization and Quality of Care -- Index.
Keywords: Medicine; Emergency medicine; Critical care medicine; Internal medicine; Medicine & Public Health; Intensive / Critical Care Medicine; Emergency medicine; Internal medicine